2020
DOI: 10.3390/jcm9123992
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Girdle Pain, Hypermobility Spectrum Disorder and Hypermobility-Type Ehlers-Danlos Syndrome: A Narrative Literature Review

Abstract: Pelvic girdle pain (PGP) refers specifically to musculoskeletal pain localised to the pelvic ring and can be present at its anterior and/or posterior aspects. Causes such as trauma, infection and pregnancy have been well-established, while patients with hypermobile joints are at greater risk of developing PGP. Research exploring this association is limited and of varying quality. In the present study we report on the incidence, pathophysiology, diagnostic and treatment modalities for PGP in patients suffering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 121 publications
0
16
0
Order By: Relevance
“…While neuropathic modulators including tricyclic antidepressants, anticonvulsants, serotonin, and norepinephrine reuptake inhibitors are traditionally useful for centralized pain, their use in this patient population is limited secondary to 47% of patients noting adverse effects including worsening dysautonomia [ 6 ]. For patients with specific pelvic pain not responsive to oral analgesia or conservative management, injection with long-acting corticosteroids can be used [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While neuropathic modulators including tricyclic antidepressants, anticonvulsants, serotonin, and norepinephrine reuptake inhibitors are traditionally useful for centralized pain, their use in this patient population is limited secondary to 47% of patients noting adverse effects including worsening dysautonomia [ 6 ]. For patients with specific pelvic pain not responsive to oral analgesia or conservative management, injection with long-acting corticosteroids can be used [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Involving a physiatrist for patients with EDS who have POP is a key component of general management. Pelvic girdle pain is common and is a result of altered biomechanics throughout the pelvis [ 7 ]. Physiotherapy attempts to restore the balance of the pelvis by strengthening, stretching, improving flexibility, and stabilizing the soft tissues [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those pregnant with hEDS/HSD can experience disabling increases in joint laxity along with a variety of urogynaecological complications (Gilliam, Hoffman, Yeh 2020). Pelvic pain and joint instability are common (Volkov et al 2018;Lind and Wallenburg 2002;Ali et al 2020) and pelvic girdle pain can be especially notable in the first trimester of pregnancy (Ahlqvist et al 2020). In our previous review, we promoted the need for early referrals to physiotherapy services and general practitioners in such cases (Pezaro, Pearce, Reinhold 2018).…”
Section: Antenatal Care Considerationsmentioning
confidence: 99%
“…The management of this can be further complicated by emotional and behavioural responses to PGP (Alappattu and Bishop 2011), and fear avoidance beliefs, which may lead to worsening levels of pain tolerance (Quartana, Campbell, Edwards 2009;Chang et al 2007;Rashidi Fakari, Simbar, Saei Ghare Naz 2018;Alappattu and Bishop 2011). Accordingly, multidisciplinary working with clinical psychology, psychiatry, pain management, physiotherapy, and rheumatology teams in line with summarised recommendations may be useful in the management of PGP (Ali et al 2020;Vleeming et al 2008). Where PGP persists, last line treatments may include intra-pelvic corticosteroid injection treatments (Lindgren 2020), and joint fusion (Vleeming et al 2008).…”
Section: Postnatal Care Considerationsmentioning
confidence: 99%
“…Probable risk factors are increased workload, inactive lifestyle, higher age in pregnancy, generalized joint hypermobility [97,98], and stress [2,7,25,62,99]. Research has shown that physically active women, regularly engaging in high-impact exercises before the first pregnancy, have a reduced risk of experiencing PGP in pregnancy [100].…”
Section: Risk Factorsmentioning
confidence: 99%